Nipple-sparing bilateral prophylactic mastectomy and immediate reconstruction with TiLoop® Bra mesh in BRCA1/2 mutation carriers: A prospective study of long-term and patient reported outcomes using the BREAST-Q. (June 2018) - Casella, D.; Di Taranto, G.; Marcasciano, M.; Sordi, S.; Kothari, A.; Kovacs, T.; Lo Torto, F.; Cigna, E.; Ribuffo, D.; Calabrese, C.
Abstract: Background: Although demand for prophylactic mastectomy is increasing over time among women at a high risk for breast cancer, there is a paucity of studies on long term patient-reported outcomes after this procedure. Methods: Between January 2011 and January 2015, 46 patients documented BRCA1/2 mutation carriers, eligible for prophylactic nipple-sparing mastectomy (NSM) and immediate breast prosthetic reconstruction were registered at our Institution. Patients underwent NSM and subcutaneous reconstruction with implant covered by a titanium-coated polypropylene mesh (TiLoop ® ). The BREAST-Q questionnaire was given to patients prior to surgery and at 1 and 2 years follow-up points. Capsular contracture was evaluated by Baker scale. Surgical outcomes along with the changes in BREAST-Q score were analyzed over time. Results: Complications were reported in only one case and after two years the capsular contracture rates were acceptable (grade I: 65, 2%; grade II: 32, 6%; grade III 2, 2%). At one year and two year follow-ups patients reported high rates in the measures of overall satisfaction with breasts (72, 5 and 73, 7 respectively), psychosocial well-being (78, 4 and 78, 6), sexual well-being (58, 8 and 59, 4), physical well-being (77, 6 and 80, 6) and overall satisfaction with outcome (75, 7 and 79, 7). A statistically significant increase in all BREAST-domains from the preoperative to the postoperative period was reported at one and two years follow-ups (p < 0, 05). Conclusion: Following bilateral prophylactic NSM and immediate subcutaneous reconstruction with TiLoop ®, patients demonstrated high levels of satisfaction and quality of life as measured by BREAST-Q. 2-years outcomes confirmed high patient comfort with increased scores from the preoperative baseline level. Highlights: Bilateral prophylactic NSM and DTI subcutaneous breast reconstruction with a titanium-coated polypropylene mesh for BRCA1/2 mutation carriers. Outcomes evaluation with preoperative and postoperative BREAST-Q modules. The technique provides acceptable complications rate and high levels of quality of life outcomes.